Insights into the spectrum of transtibial prosthetic socket design from expert clinicians and their digital records - Dickinson, A. S.; Steer, J. W.; Rossides, C.; Diment, L. E.; Mbithi, F. M.; Bramley, J. L.; Hannett, D.; Blinova, J.; Tankard, Z.; Worsley, P. R. (Frontiers in Rehabilitation Sciences, 2024)
Background: transtibial prosthetic sockets are often grouped into patella tendon bearing (PTB) or total surface bearing (TSB) designs, but many variations in rectifications are used to personalise the prosthetic limb to the individual. Prosthetists currently have little objective evidence to assist them as they make design choices. Aims: to compare rectifications made by experienced prosthetists across a range of patient demographics and limb shapes to improve understanding of socket design strategies. Methodology: residual limb surface scans and 163 CAD/CAM sockets were analysed for 134 randomly selected individuals in a UK prosthetics service. This included 142 PTB and 21 TSB designs. The limb and socket scans were compared to determine the location and size of rectifications. Rectifications were compiled for PTB and TSB designs, and associations between different rectification sizes were assessed using a variety of methods including linear regression, kernel density estimation (KDE) and a Naïve Bayes (NB) classification. Results: differences in design features were apparent between PTB and TSB sockets, notably for paratibial carves, gross volume reduction and distal end elongation. However, socket designs varied across a spectrum, with most showing a hybrid of the PTB and TSB principles. Pairwise correlations were observed between the size of some rectifications (e.g. paratibial carves; fibular head build and gross volume reduction). Conversely, the patellar tendon carve depth was not associated significantly with any other rectification, indicating its relative design insensitivity. The Naïve Bayes classifier produced design patterns consistent with expert clinician practice. For example, subtle local rectifications were associated with a large volume reduction (i.e. a TSB-like design), whereas more substantial local rectifications (i.e. a PTB-like design) were associated with a low volume reduction. Clinical implications: this study demonstrates how we might learn from design records to support education and enhance evidence-based socket design. The method could be used to predict design features for newly presenting patients, based on categorisations of their limb shape and other demographics, implemented alongside expert clinical judgement as smart CAD/CAM design templates.